The influence of edge radius and lead content on machining performance of brass alloys - KAYNAK, YUSUF (My University, 2022)
© 2022 Elsevier B.V.. All rights reserved.Considering industrial applications, three main brass alloys including lead-free, low-lead and leaded are being deployed. However, as these materials are used in potable water applications, low-lead and lead-free brass alloy are becoming preferred to leaded ones due to their health effect. On the other hand, Lead is the element increases machinability of such materials. Machining efficiency of these type materials can be raised by using round edge cutting tools. This paper presents experimental results of the machining performance of lead-free, low-lead and leaded brass alloys in terms of cutting forces, surface roughness, and burr height during milling operations. Moreover, it also takes into account the edge radius of cutting tools and its role on machining the performance. Empirical equations are derived to predict the machining behavior for each material. Increasing the edge radius results in larger cutting forces and tool vibration during the process, but better surface quality. Furthermore, reduction/elimination of the Lead element in alloy content has concluded into higher burr size on the machined surface edges.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); ENGINEERING; AUTOMATION & CONTROL SYSTEMS; ENGINEERING, MANUFACTURING; Fizik Bilimleri; Endüstri ve İmalat Mühendisliği; Control and Systems Engineering; Physical Sciences; Industrial and Manufacturing Engineering; Brass alloys; burr formation; cutting-edge radius; flat endmill; machining